The Hahn Banach theorem in convex programming - Ferreira, M. (14th Conference on Applied Mathematics APLIMAT 2015 Proceedings, 2015)
Separation theorems are the fundamentals of convex programming.They are important consequences of Hahn-Banach theorem. This work begins considering vector spaces, in broad sense, then normed spaces and finally Hilbert spaces. It ends with the application of these results in convexprogramming, an important tool in operations research, finance, management and economics.